Anatomical and Functional Recovery of Intracapsular Fractures of the Mandibular Condyle: Analysis of 124 Cases after Closed Treatment - Lee, Jong-Sung (Maxillofac Plast Reconstr Surg, 2014)
PURPOSE: The purpose of this study is to evaluate the influence of intracapsular fracture lines of the mandibular condyle on the anatomical and functional recovery after non-surgical closed treatment. METHODS: Clinical and radiological follow-up of 124 patients with intracapsular fractures of the mandibular condyle was performed after closed treatment between 2005 and 2012. The intracapsular fractures were classified into three categories: type A (medial condylar pole fracture), type B (lateral condylar pole fracture with loss of vertical height) and type M (multiple fragments or comminuted fracture). RESULTS: By radiological finding, fracture types B and M lost up to 24% vertical height of the mandibular condyle compared to the height on the opposite side. In Type M, moderate to severe dysfunction was observed in 33% of the cases. Bilateral fractures were significantly associated with the risk of temporomandibular joint (TMJ) dysfunction in fracture types A and B. Bilateral fracture and TMJ dysfunction were not statistically significantly associated in type M fractures. CONCLUSION: Most of the mandibular intracapsular condylar fractures recovered acceptably after conservative non-surgical treatment with functional rehabilitation, even with some anatomical shortening of the condylar height. The poor functional recovery encountered in type M fractures, especially in cases with additional fracture sites and bilateral fractures, points up the limitation of closed treatment in such cases.